Women Terrorist Interests in the ISIS Movement: A Case Study in Indonesia - Sabrina Malia Rohali; Gonda Yumitro (Jurnal Studi Sosial dan Politik, 2022)
This article aims to find out the interest of women's terrorism in the ISIS movement. This research is explanatory research with data collection through library research or literature study through Google Scholar, Harzing's Publish or Perish, and other journals to publish data from 2012 to August 2021. There are several reasons for female terrorism's involvement in the ISIS political movement in Indonesia, which include family reasons, efforts to create equal rights for men and women, the existence of narcissistic personality forms, psychopathology, and religious fanatics. Even in the interests of the movement, women's terrorism is an easy target in acts of terrorism. It can be seen from how women are difficult to suspect in terrorist acts, thus making the officers and the public careless in monitoring. Sometimes they even involve their children in tricking the security forces. In this article, the authors used a feminist approach to understand the interests of women in the ISIS political movement in Indonesia.